2018
DOI: 10.3758/s13414-018-1484-0
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial legend compatibility within versus between graphs in multiple graph comprehension

Abstract: Previous research has shown that spatial compatibility between the data region and the legend of a graph is beneficial for comprehension. However, in multiple graphs, data-legend compatibility can come at the cost of spatial between-graph legend incompatibility. Here we aimed at determining which type of compatibility is most important for performance: global (legend-legend) compatibility between graphs, or local (data-legend) compatibility within graphs. Additionally, a baseline condition (incompatible) was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Future studies should use more data points with different numbers of trend reversals (i.e., slopes of adjacent lines from positive to negative or vice-versa), as it was shown that they have an impact on comprehension time (Carswell et al, 1993 ). Future studies should also examine how schema switches might affect graph processing when a single task involves comparisons between multiple (similar or different) graphs, that is, in complex graph display (e.g., see Riechelmann and Huestegge, 2018 ; Poetzsch et al, 2020 ). Other types of tasks should be used in future studies, such as a more basic “which is larger” comparison, A + B vs. C + D, as pie charts are ideal to combine even non-adjacent slices compared to summing up heights in bar graphs (Spence and Lewandowsky, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should use more data points with different numbers of trend reversals (i.e., slopes of adjacent lines from positive to negative or vice-versa), as it was shown that they have an impact on comprehension time (Carswell et al, 1993 ). Future studies should also examine how schema switches might affect graph processing when a single task involves comparisons between multiple (similar or different) graphs, that is, in complex graph display (e.g., see Riechelmann and Huestegge, 2018 ; Poetzsch et al, 2020 ). Other types of tasks should be used in future studies, such as a more basic “which is larger” comparison, A + B vs. C + D, as pie charts are ideal to combine even non-adjacent slices compared to summing up heights in bar graphs (Spence and Lewandowsky, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on data visualization was first concerned with the optimization of single chart visualizations, starting with Eells (1926). Corresponding research on data encoding effectiveness peaked in the 80s and 90s, when landmark studies like those by Cleveland and McGill (1984), who invented dot plots, or by Hollands and Spence (1992), who evaluated line charts vs. bar charts as the most effective means to communicate change in data (see also Huestegge and Philipp, 2011;Riechelmann and Huestegge, 2018), emerged. Scatterplots, on the other hand, were later considered an optimal choice for visualizing correlations (Harrison et al, 2014;Kay and Heer, 2016).…”
Section: Background and Previous Workmentioning
confidence: 99%